“Are you safe?”: Using the regulatory focus theory to understand Indian heterosexual and queer dating app users’ strategies to mitigate the risks of online dating - Bose, C.; George, P.; Epton, T.; Siddiqui, H.; Rodrigues, D. L.; Chittem, M. (Psychology and Sexuality)
This study examined how Indian dating app users perceive risks in their online interactions and the strategies they employed to mitigate deception, privacy concerns, and protect their sexual health, framed by Regulatory Focus Theory (RFT) assumptions. Semi-structured, audio-recorded interviews (N = 10) were conducted with heterosexual (n = 4) and queer (n = 6) urban Indian dating app users. Interviews explored participants’ risk-related decision-making regarding matching, meeting, and engaging in sexual activity with a potential partner, and methods used to mitigate risks. Data were analysed using interpretative phenomenological analysis. Three major themes were identified, with risk mitigation strategies related to: (i) deception – pertaining to the idea of ‘trust’ and safety’ while interacting with other users, (ii) privacy or identity maintenance – unique to queer individuals wherein they used a range of strategies (e.g. anonymising identity), and (iii) sexual health protection – participants tried to establish trust and engaged in condom negotiation. Aligned with RFT, these findings demonstrate that dating app users oscillate between prevention-focused (avoiding deception and protecting privacy) and promotion-focused (pursuing intimacy and maintaining sexual health) strategies. Overall, this study highlights a need for improving access to sexual health clinics, nesting safety/security measures within dating apps, and designing interventions to address users’ diverse motives in dating app use.